Dispersion, curable resin composition, dry film, cured product, and printed circuit board

JP2026165949APending Publication Date: 2026-10-14TAIYO HOLDINGS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025058615
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、硫酸バリウムの分散性と経時安定性に優れる分散液が得られ、硬化性樹脂組成物、ドライフィルムの樹脂層中にフィラーとして含まれる硫酸バリウムの分散性、経時安定性を向上させることができ、硬化物及びプリント配線板におけるクラックや剥れを好適に防止することができるようになる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165949000001
    Figure 2026165949000001
Patent Text Reader

Abstract

The present invention provides a dispersion liquid with excellent dispersibility and long-term stability, using barium sulfate as a filler. [Solution] The above problem is solved by a dispersion containing barium sulfate, a dispersant having a branched polyamine, a dispersant having polyurethane, and a solvent, wherein the barium sulfate content is 50 to 80% by mass of the total volume of the dispersion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a dispersion, a curable resin composition, a dry film, a cured product, and a printed wiring board.

Background Art

[0002] Printed wiring boards used in electronic devices and the like are provided with a solder resist layer for the purpose of preventing solder from adhering to unnecessary portions when mounting electronic components. The solder resist layer is formed by applying a curable resin composition to a substrate and curing predetermined positions. Examples of methods for applying the curable resin composition to the substrate include a method of applying the curable resin composition to the substrate as a solder resist ink, and a method of laminating a dry film having a resin layer obtained by applying the curable resin composition onto a carrier film and drying the same onto the substrate.

[0003] This curable resin composition may contain various fillers such as barium sulfate and silica in order to improve various properties such as rigidity, heat resistance, coating film strength, and adhesion to the substrate of the solder resist layer, and to prevent cracks and peeling caused by the difference in coefficient of thermal expansion between the solder resist layer and the substrate. When a filler is contained in the curable resin composition, if the filler aggregates in the curable resin composition, it leads to poor appearance of the solder resist layer and deterioration of resolution during curing. Therefore, for the purpose of improving the dispersibility of the filler in the curable resin composition, a dispersion in which the filler is dispersed in advance is separately produced and blended.

[0004] Since this dispersion is to be blended with other compositions when producing the curable resin composition, it is required to have a high filler content (for example, 50% by mass or more based on the total amount of the dispersion), be uniformly dispersed without aggregation, precipitation or solidification of the filler, and further have temporal stability that maintains the dispersibility of the filler from after production until use.

Prior Art Documents

Patent Documents

[0005] [Patent Document 1] Japanese Patent Publication No. 2000-181058 [Patent Document 2] Japanese Patent Publication No. 2002-080818 [Overview of the project] [Problems that the invention aims to solve]

[0006] However, while barium sulfate, known as a filler, has advantages such as excellent chemical stability including heat resistance and chemical resistance, as well as easy availability, its high specific gravity makes it prone to viscosity changes over time due to sedimentation, posing a challenge to its long-term stability. Furthermore, increasing the blending ratio results in a highly viscous paste that is difficult to circulate in dispersion processes such as bead mills once mixed with the solvent, making it difficult to achieve a dispersed state.

[0007] Therefore, the main object of the present invention is to provide a dispersion of barium sulfate that is excellent in dispersibility and stability over time, a curable resin composition containing the dispersion, a dry film having a resin layer obtained from the curable resin composition, a cured product of the resin layer of the curable resin composition or the dry film, and a printed circuit board having the cured product. [Means for solving the problem]

[0008] The inventors diligently studied to solve the above problems. As a result, they found that by using a dispersant containing a branched polyamine and a dispersant containing polyurethane in combination, a dispersion with excellent dispersibility of barium sulfate and stability over time can be obtained. Based on this finding, further studies led to the completion of the present invention.

[0009] In other words, the present invention relates to the following dispersions, curable resin compositions, dry films, cured products, and printed circuit boards. [1] A dispersion comprising barium sulfate, a dispersant having a branched polyamine, a dispersant having polyurethane, and a solvent, wherein the barium sulfate content is 50 to 80% by mass of the total volume of the dispersion. [2] The dispersion according to [1] above, wherein the average particle size of barium sulfate in the dispersion is 0.1 μm to 5 μm. [3] A curable resin composition characterized by comprising a curable resin and a dispersion of the above [1] or [2]. [4] A dry film comprising a first film and a resin layer formed from any of the curable resin compositions described in [1] to [3] above, laminated on at least one surface of the first film. [5] A cured product characterized by being obtained by curing any of the curable resin compositions described in [1] to [3] above. [6] A cured product characterized by having been obtained by curing the resin layer of the dry film described in [4] above. [7] A printed circuit board characterized by containing the cured product described in [5] above. [8] A printed circuit board characterized by containing the cured product described in [6] above. [Effects of the Invention]

[0010] According to the present invention, a dispersion liquid with excellent dispersibility and stability over time for barium sulfate can be obtained, improving the dispersibility and stability over time of barium sulfate contained as a filler in curable resin compositions and dry film resin layers, thereby effectively preventing cracks and peeling in cured products and printed circuit boards. [Modes for carrying out the invention]

[0011] The dispersion, curable resin composition, dry film, cured product, and printed circuit board of the present invention are described below. In this specification, "(meth)acrylate" is a general term for acrylate, methacrylate, and mixtures thereof, and the same applies to other similar expressions ((meth)acrylic acid, (meth)acryloyl, etc.). Also, when a numerical range is expressed using "~" such as "A~B", unless otherwise specified, this means "A or greater and B or less". [Dispersion] The dispersion of the present invention uses barium sulfate as a filler and contains two types of dispersants: a dispersant having a branched polyamine and a dispersant having a polyurethane, and a solvent. (Barium sulfate) Barium sulfate is highly suitable as a filler due to its high heat resistance, chemical resistance, and water resistance, its chemical stability, its white color, and its high availability. The presence or absence of surface treatment of the barium sulfate used in the dispersion of the present invention is not necessarily limited. Surface treatment may or may not be performed. However, surface treatment is preferable because it can more effectively suppress aggregation. The method of surface treatment of barium sulfate is not particularly limited, and any known and conventional method may be used. Examples include surface treatment with SiO2 and Al2O3, and surface treatment with a surface treatment agent having a curable reactive group. As for surface treatment with a surface treatment agent having a curable reactive group, a method of treating the surface of barium sulfate with a coupling agent having a curable reactive group as an organic group is mentioned. A preferred surface treatment is surface treatment with SiO2 and Al2O3.

[0012] The amount of barium sulfate in the dispersion is 50 to 80% by mass of the total volume of the dispersion, more preferably 60 to 80% by mass, and even more preferably 65 to 75% by mass. A dispersion containing 50% by mass or more of barium sulfate can be said to have a high barium sulfate content and can be considered a dispersion containing a sufficient amount of filler for use in thermosetting resin compositions. If the amount of barium sulfate is less than 50% by mass, problems such as dispersibility are easier to resolve, but a large amount of dispersion is required to incorporate the filler into the curable resin composition, which is undesirable in terms of yield. Furthermore, if it exceeds 80% by mass, it becomes difficult to obtain a slurry suitable for use as a dispersion.

[0013] The average particle size of barium sulfate in the dispersion of the present invention is preferably 0.1 μm to 5.0 μm. More preferably 0.1 to 2.0 μm, and even more preferably 0.15 to 1.0 μm. When the average particle size of barium sulfate in the dispersion is within the above range, the dispersion state is more easily maintained, resulting in superior stability over time. This average particle size of barium sulfate is the average particle size (D50) that includes not only the particle size of primary particles but also the particle size of secondary particles (aggregates), and is the D50 value measured by laser diffraction. An example of a laser diffraction measuring device is the Microtrac MT3300EXII manufactured by Nikkiso Co., Ltd.

[0014] (Dispersant) The dispersion of the present invention contains two types of dispersants: a dispersant having a characteristically branched polyamine and a dispersant having a polyurethane. Although the mechanism by which the combined use of these dispersants improves the dispersibility and long-term stability of barium sulfate is not entirely clear, it is believed that these dispersants interact with each other, and that the combined effects of reduced viscosity of the dispersion and de-aggregation of barium sulfate due to steric hindrance improve the dispersibility and long-term stability of barium sulfate.

[0015] The dispersant containing branched polyamines in the dispersion of the present invention is effective in that it provides an anti-aggregation effect due to steric hindrance. Examples of branched polyamines in the dispersant containing branched polyamines include aliphatic polyamines such as polyallylamine, polyvinylamine, polyethyleneimine, and poly(trimethyleneimine), and polyamides having amino groups in their side chains, such as polylysine and polyarginine. These branched polyamines may be used individually or in combination of two or more. Specific examples of dispersants containing branched polyamines include BYK-9076, DISPERBYK(registered trademark)-140, 142, 145, 2152, 2157, 2158, 2200, and 2205 (all manufactured by Bic Chemie). The proportion of the dispersant containing polyamines in the dispersion is not necessarily limited, but is preferably 0.3% to 3.0% by mass relative to the total volume of the dispersion. Furthermore, while the amine value and acid value of branched polyamines are not necessarily limited, it is desirable that the amine value be 50 mgKOH / g or higher and the acid value be 50 mgKOH / g or higher.

[0016] The dispersant having a polyurethane contained in the dispersion of the present invention is effective in adjusting the viscosity in the dispersion. The weight average molecular weight of the dispersant having a polyurethane is preferably a polyurethane-based dispersant of 1,000 to 100,000, more preferably a polyurethane-based dispersant having a weight average molecular weight of 5,000 to 50,000. The blending ratio of the dispersant having a polyurethane in the dispersion is not necessarily limited, but is preferably 0.5 mass% to 2.5 mass%. Specific examples of the dispersant having a polyurethane include DISPERBYK (registered trademark)-161, 162, 163, 164, 167, 168, 170, 171, 174, 182, 184, 185, 2150, 2152, 2155, 2163, 2164, and BYK-9077 (all manufactured by BYK-Chemie GmbH). The blending ratio of the dispersant having a polyurethane is not necessarily limited, but is preferably 1.0 mass% to 6.0 mass% relative to the total amount of the dispersion. The amine value and acid value of the polyurethane are not necessarily limited, but it is desirable that at least one of the amine value of 10 mgKOH / g or more and the acid value of 10 mgKOH / g or more is satisfied. Further, from the viewpoint of temporal stability, the preferred ratio of the dispersant having a branched polyamine and the dispersant having a polyurethane contained in the dispersion of the present invention is preferably from 1:9 to 1:1, more preferably from 1:4 to 2:3, and even more preferably from 1:3 to 1:2.

[0017] The dispersion of the present invention may contain a dispersant other than the dispersant having a branched polyamine and the dispersant having a polyurethane. Examples of other dispersants include dispersants having a phosphate ester. The dispersant having a phosphate ester makes viscosity adjustment easier. Examples of the dispersant having a phosphate ester include DISPERBYK (registered trademark)-102, 103, 106, 110, 118, 160 (all manufactured by BYK-Chemie GmbH).

[0018] (Solvent) The dispersion contains a solvent for preparing the barium sulfate to an appropriate dispersion state. Organic solvents are preferred as the solvent, and examples include ketones, aromatic hydrocarbons, glycol ethers, glycol ether acetates, esters, alcohols, aliphatic hydrocarbons, and petroleum-based solvents. More specifically, these include ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, diethylene glycol monoethyl ether acetate (carbitol acetate), dipropylene glycol methyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, and propylene glycol butyl ether acetate; alcohols such as ethanol, propanol, ethylene glycol, and propylene glycol; aliphatic hydrocarbons such as octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha. The solvent may be used alone or as a mixture of two or more. Preferably, it is dipropylene glycol monomethyl ether or diethylene glycol monoethyl ether acetate (carbitol acetate), and particularly preferred in terms of the dispersibility of barium sulfate is dipropylene glycol monomethyl ether.

[0019] (Method for producing dispersion) The dispersion of the present invention can be produced by mixing barium sulfate, a dispersant and a solvent, followed by a dispersion step using a bead mill or a jet mill. It is preferably produced through a dispersion step using a bead mill. Examples of the type of beads in the bead mill include zirconia beads, alumina beads and the like. The particle diameter of the beads is, for example, in the range of φ0.015 to 2.0 mm. Among these, the range of φ0.1 to 1.5 mm is more preferable. The filling rate of the beads is 50 to 95%, and the viscosity at the time of charging into the bead mill is preferably less than 10 Pa·s from the viewpoints of improving dispersibility and obtaining a cured coating film with lower gloss. On the other hand, the lower limit is preferably 0.1 Pa·s or more. More preferably, the viscosity in the present invention is a value measured with a cone-plate type viscometer (TVE-33H, manufactured by Toki Sangyo Co., Ltd.) using a 3° × R9.7 cone rotor under conditions of 50°C, 100 rpm, and 30 seconds, in accordance with the viscosity measurement method using a 10° cone-plate rotational viscometer specified in JIS Z 8803:2011.

[0020] (Additives) The dispersion of the present invention may contain known additives within a range that does not impair the effects of the present invention. Examples of the additives include at least one of antifoaming agents and leveling agents such as silicone-based, fluorine-based and polymer-based agents, silane coupling agents such as imidazole-based, thiazole-based and triazole-based agents, rust inhibitors, thickeners and the like.

[0021] [Curable Resin Composition] Next, the curable resin composition of the present invention will be described. The curable resin composition of the present invention comprises a curable resin and the above-mentioned dispersion, and contains barium sulfate as a filler. By using the above-mentioned dispersion, the temporal stability of the curable resin composition and the dispersibility of barium sulfate, which is the filler in the curable resin composition, are improved, and various properties such as rigidity, heat resistance, coating strength, and adhesion to the substrate of the solder resist layer, which is a cured product obtained by curing this curable resin composition, can be suitably improved. In the case of a thermosetting resin composition, the curable resin composition may contain a thermosetting compound and a thermosetting catalyst in addition to the filler. Furthermore, to be photocurable and alkali soluble, it may contain an alkali soluble resin, a photopolymerizable monomer, and a photopolymerization initiator. In the case of a photocurable resin composition, it may also contain a photopolymerizable monomer and a photopolymerization initiator in addition to the filler. The curable resin composition according to the present invention may further contain a curing agent, a colorant, an organic solvent, etc.

[0022] (Filler) The curable resin composition of the present invention contains barium sulfate derived from the dispersion of the present invention as a filler (inorganic filler). By including barium sulfate derived from the dispersion of the present invention as a filler, various properties such as adhesion, heat resistance, and coating strength of the curable resin composition can be effectively improved. Furthermore, the curable resin composition of the present invention may also contain fillers other than barium sulfate derived from the dispersion of the present invention. For example, silica (SiO2), alumina (Al2O3), titania (TiO2), tantalum oxide (Ta2O5), zirconia (ZrO2), silicon nitride (Si3N4), barium titanate (BaO·TiO2), barium carbonate (BaCO3), magnesium carbonate, aluminum hydroxide, magnesium hydroxide, lead titanate (PbO·TiO2), lead zirconate titanate (PZT), lead lanthanum zirconate titanate (PLZT), gallium oxide (Ga2O3), spinel (MgO·Al2O3), mullite (3Al2 Preferred materials include O3·2SiO2), cordierite (2MgO·2Al2O3·5SiO2), talc (3MgO·4SiO2·H2O), aluminum titanate (TiO2·Al2O3), yttria-containing zirconia (Y2O3·ZrO2), barium silicate (BaO·8SiO2), boron nitride (BN), calcium carbonate (CaCO3), calcium sulfate (CaSO4), zinc oxide (ZnO), magnesium titanate (MgO·TiO2), hydrotalcite, mica, calcined kaolin, and carbon. These can be used individually or in combination of two or more. Furthermore, these materials may be surface-treated or unsurface-treated.

[0023] The average particle size of fillers other than barium sulfate derived from the dispersion of the present invention can be, for example, 0.1 to 10.0 μm, preferably 0.1 to 2.0 μm. The average particle size of the fillers is the average particle size (D50) including not only the primary particle size but also the secondary particle size (aggregate) size, and is the D50 value measured by laser diffraction. An example of a laser diffraction measuring device is the Microtrac MT3300EXII manufactured by Microtrac-Bell Corporation.

[0024] Furthermore, it is preferable to pre-disperse and prepare fillers other than barium sulfate derived from the dispersion of the present invention, for example, using a bead mill or jet mill. It is also preferable to incorporate them in slurry form, as incorporating them as a slurry dispersion facilitates high dispersion, prevents aggregation, and makes handling easier.

[0025] The total content of barium sulfate derived from the dispersion of the present invention, or other fillers combined, in the curable resin composition is preferably 10 to 70% by mass, and more preferably 15 to 70% by mass, based on the solid content relative to the total amount of the curable resin composition.

[0026] (thermosetting compound) The curable resin composition of the present invention may contain a thermosetting compound as the curable compound. When a thermosetting compound is included, the heat resistance of the cured product is improved, and the adhesion to the substrate is also improved. As the thermosetting compound, known and conventional thermosetting compounds such as isocyanate compounds, blocked isocyanate compounds, amino resins, benzoxazine resins, carbodiimide resins, cyclocarbonate compounds, epoxy compounds, polyfunctional oxetane compounds, and episulfide resins can be used. Among these, epoxy compounds, polyfunctional oxetane compounds, and episulfide resins are preferred, and epoxy compounds are more preferred. The thermosetting compound can be used alone or in combination of two or more.

[0027] The epoxy compounds mentioned above are compounds having epoxy groups, and any conventionally known ones can be used. Examples include polyfunctional epoxy resins having multiple epoxy groups in the molecule. Hydrogenated epoxy resins may also be used.

[0028] Examples of polyfunctional epoxy resins include epoxidized vegetable oils; bisphenol A type epoxy resins; hydroquinone type epoxy resins; bisphenol type epoxy resins; thioether type epoxy resins; brominated epoxy resins; novolac type epoxy resins; biphenol novolac type epoxy resins; bisphenol F type epoxy resins; hydrogenated bisphenol A type epoxy resins; glycidylamine type epoxy resins; hydantoin type epoxy resins; alicyclic epoxy resins; trihydroxyphenylmethane type epoxy resins; bixylenol type or biphenol type epoxy resins or mixtures thereof. Examples of epoxy resins include, but are not limited to, bisphenol S type epoxy resins; bisphenol A novolac type epoxy resins; tetraphenyloleethane type epoxy resins; heterocyclic epoxy resins; diglycidyl phthalate resins; tetraglycidyl xylenoylethane resins; naphthalene group-containing epoxy resins; epoxy resins having a dicyclopentadiene skeleton; glycidyl methacrylate copolymer epoxy resins; copolymer epoxy resins of cyclohexylmaleimide and glycidyl methacrylate; epoxy-modified polybutadiene rubber derivatives; and CTBN-modified epoxy resins. These epoxy resins can be used individually or in combination of two or more. Among these, novolac type epoxy resins, bisphenol type epoxy resins, bixylenol type epoxy resins, biphenol type epoxy resins, biphenol novolac type epoxy resins, naphthalene type epoxy resins, or mixtures thereof are particularly preferred.

[0029] Examples of polyfunctional oxetane compounds include bis[(3-methyl-3-oxetanylmethoxy)methyl] ether, bis[(3-ethyl-3-oxetanylmethoxy)methyl] ether, 1,4-bis[(3-methyl-3-oxetanylmethoxy)methyl]benzene, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, (3-methyl-3-oxetanyl)methyl acrylate, (3-ethyl-3-oxetanyl)methyl Examples include polyfunctional oxetanes such as acrylates, (3-methyl-3-oxetanyl)methyl methacrylate, (3-ethyl-3-oxetanyl)methyl methacrylate, and their oligomers or copolymers, as well as ethers of oxetane alcohols with resins having hydroxyl groups such as novolac resins, poly(p-hydroxystyrene), cardo-type bisphenols, calixarenes, calixresorcinarenes, or silsesquioxane. Other examples include copolymers of unsaturated monomers having an oxetane ring with alkyl (meth)acrylates.

[0030] Examples of episulfide resins include bisphenol A type episulfide resins. Furthermore, episulfide resins obtained by replacing the oxygen atoms in the epoxy groups of novolac type epoxy resins with sulfur atoms using a similar synthesis method can also be used.

[0031] The content of the thermosetting compound is preferably 3.0 to 30% by mass, more preferably 4.0 to 25% by mass, and even more preferably 5.0 to 20% by mass, based on the solid content of the total curable resin composition.

[0032] (Thermosetting catalyst) The curable resin composition of the present invention may contain a thermosetting catalyst, to the extent that it does not impair the properties of the present invention. Examples of such thermosetting catalysts include imidazole derivatives such as imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, and 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole; amine compounds such as dicyandiamide, benzyldimethylamine, 4-(dimethylamino)-N,N-dimethylbenzylamine, 4-methoxy-N,N-dimethylbenzylamine, and 4-methyl-N,N-dimethylbenzylamine; hydrazine compounds such as adipic acid dihydrazide and sebacate dihydrazide; and phosphorus compounds such as triphenylphosphine. Furthermore, guanamine, acetoganaamine, and benzoguanamine can also be used, and preferably these compounds, which also function as adhesion promoters, can be used in combination with the thermosetting catalyst. As can be seen from this, the thermosetting catalyst may be used alone or in combination of two or more types.

[0033] The content of the thermosetting catalyst can be, in terms of solid content, for example, more than 0 and up to 20 parts by mass per 100 parts by mass of the thermosetting compound, preferably 0.05 to 20 parts by mass, and more preferably 0.1 to 15 parts by mass.

[0034] (Alkali-soluble resin) The curable resin composition of the present invention may contain an alkali-soluble resin. The alkali-soluble resin is a resin containing an alkali-soluble group in its molecule, and various known resins can be used, such as a resin containing one or more alkali-soluble groups selected from the group consisting of phenolic hydroxyl groups and carboxyl groups. Specifically, examples of alkali-soluble resins include carboxyl group-containing resins, phenolic hydroxyl group-containing resins (particularly resins containing two or more phenolic hydroxyl groups), and resins containing both phenolic hydroxyl groups and carboxyl groups.

[0035] As for alkali-soluble resins, carboxyl group-containing resins are preferred from the viewpoint of developability, photocurability, and developability, and resins containing two or more carboxyl groups are more preferred. It is particularly preferable that the alkali-soluble resin contains ethylenically unsaturated groups in addition to carboxyl groups. The ethylenically unsaturated groups are preferably derived from acrylic acid, methacrylic acid, or their derivatives. This carboxyl group-containing resin having ethylenically unsaturated groups may hereafter be referred to as "carboxyl group-containing photosensitive resin." Note that only carboxyl group-containing resins without ethylenically unsaturated groups may be used as alkali-soluble resins. If the carboxyl group-containing resin does not have ethylenically unsaturated groups, a compound having multiple ethylenically unsaturated groups in its molecule, i.e., a photopolymerizable monomer, can be used in combination to make the curable resin composition photocurable.

[0036] Specific examples of alkali-soluble resins include the compounds listed below. These compounds may be either oligomers or polymers. Examples of carboxyl group-containing resins include the following compounds, which may be used individually or in combination of two or more. (1) A carboxyl group-containing resin obtained by copolymerization of an unsaturated carboxylic acid such as (meth)acrylic acid with an unsaturated group-containing compound such as styrene, α-methylstyrene, lower alkyl (meth)acrylate, or isobutylene.

[0037] (2) A carboxyl group-containing urethane resin obtained by polyaddition reaction of diisocyanates such as aliphatic diisocyanates, branched aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates with carboxyl group-containing dialcohol compounds such as dimethylolpropionic acid and dimethylolbutanoic acid, and diol compounds such as polycarbonate polyols, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, bisphenol A alkylene oxide adduct diols, and compounds having phenolic hydroxyl groups and alcoholic hydroxyl groups.

[0038] (3) A carboxyl group-containing urethane resin obtained by polyaddition reaction of a diisocyanate with a partially acid anhydride modified product of a reaction between a difunctional epoxy resin such as bisphenol A type epoxy resin, hydrogenated bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bixylenol type epoxy resin, and biphenol type epoxy resin, and a monocarboxylic acid compound having an ethylenically unsaturated double bond such as (meth)acrylic acid, and a carboxyl group-containing dialcohol compound and a diol compound.

[0039] (4) A carboxyl group-containing photosensitive urethane resin obtained by adding a compound having one hydroxyl group and one or more (meth)acryloyl groups in the molecule, such as hydroxyalkyl (meth)acrylate, during the synthesis of the resin of (2) or (3) above, and then (meth)acrylicating the terminal (meth)acrylic.

[0040] (5) A carboxyl group-containing photosensitive urethane resin obtained by adding a compound having one isocyanate group and one or more (meth)acryloyl groups in its molecule, such as an equimolar reaction product of isophorone diisocyanate and pentaerythritol triacrylate, to the synthesis of the resin of (2) or (3) above, and then (meth)acrylicating the terminal (meth)acrylic.

[0041] (6) A carboxyl group-containing photosensitive resin obtained by reacting a bifunctional or polyfunctional epoxy resin with (meth)acrylic acid and adding a dibasic acid anhydride such as phthalic anhydride, tetrahydrophthalic anhydride, or hexahydrophthalic anhydride to the hydroxyl groups present in the side chain. Here, the bifunctional or polyfunctional epoxy resin is preferably solid.

[0042] (7) A carboxyl group-containing photosensitive resin obtained by reacting a polyfunctional epoxy resin, in which the hydroxyl groups of a bifunctional epoxy resin are further epoxidized with epichlorohydrin, with (meth)acrylic acid, and then adding a dibasic acid anhydride to the resulting hydroxyl groups. Here, the bifunctional epoxy resin is preferably solid.

[0043] (8) A carboxyl group-containing polyester resin obtained by reacting a bifunctional oxetane resin with dicarboxylic acids such as adipic acid, phthalic acid, and hexahydrophthalic acid, and adding dibasic acid anhydrides such as phthalic anhydride, tetrahydrophthalic anhydride, and hexahydrophthalic anhydride to the resulting primary hydroxyl groups.

[0044] (9) A carboxyl group-containing photosensitive resin obtained by reacting an epoxy compound having two or more epoxy groups in one molecule with a compound having at least one alcoholic hydroxyl group and one phenolic hydroxyl group in one molecule, such as p-hydroxyphenethyl alcohol, and an unsaturated group-containing monocarboxylic acid such as (meth)acrylic acid, and then reacting the alcoholic hydroxyl group of the reaction product with a polybasic acid anhydride such as maleic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, or adipic anhydride.

[0045] (10) A carboxyl group-containing photosensitive resin obtained by reacting a reaction product obtained by reacting a compound having two or more phenolic hydroxyl groups in one molecule, such as bisphenol A, bisphenol F, bisphenol S, novolac-type phenolic resin, poly-p-hydroxystyrene, a condensate of naphthol and aldehydes, or a condensate of dihydroxynaphthalene and aldehydes, with an alkylene oxide such as ethylene oxide or propylene oxide, with an unsaturated group-containing monocarboxylic acid such as (meth)acrylic acid, and then reacting the resulting reaction product with a polybasic acid anhydride.

[0046] (11) A carboxyl group-containing photosensitive resin obtained by reacting a reaction product obtained by reacting a compound having two or more phenolic hydroxyl groups in one molecule with a cyclic carbonate compound such as ethylene carbonate or propylene carbonate with an unsaturated group-containing monocarboxylic acid, and then reacting the resulting reaction product with a polybasic acid anhydride.

[0047] (12) A carboxyl group-containing photosensitive resin obtained by adding a compound having one epoxy group and one or more (meth)acryloyl groups in one molecule to one or more resins selected from the group consisting of (1) to (11).

[0048] When the alkali-soluble resin is a carboxyl group-containing resin, its acid value is preferably 40 to 150 mg KOH / g. Setting the acid value of the carboxyl group-containing resin to 40 mg KOH / g or higher improves alkali developability. Setting the acid value to 150 mg KOH / g or lower makes it easier to draw a normal cured pattern. The acid value of the carboxyl group-containing resin is more preferably 50 to 130 mg KOH / g.

[0049] The phenolic hydroxyl group-containing resin is not particularly limited as long as it has phenolic hydroxyl groups, i.e., hydroxyl groups bonded to a benzene ring, in its main chain or side chain. Preferably, the phenolic hydroxyl group-containing resin is a resin containing two or more phenolic hydroxyl groups in one molecule. Resins containing two or more phenolic hydroxyl groups in one molecule include, but are not limited to, catechol, resorcinol, hydroquinone, dihydroxytoluene, naphthalenediol, t-butylcatechol, t-butylhydroquinone, pyrogallol, phloroglucinol, bisphenol A, bisphenol F, bisphenol S, biphenol, bixylenol, novolac-type phenol resins, novolac-type alkylphenol resins, novolac resins of bisphenol A, dicyclopentadiene-type phenol resins, Xylok-type phenol resins, terpene-modified phenol resins, polyvinylphenols, condensates of phenols and aromatic aldehydes having phenolic hydroxyl groups, and condensates of 1-naphthol or 2-naphthol and aromatic aldehydes.

[0050] The weight-average molecular weight of alkali-soluble resins varies depending on the resin skeleton, but is generally preferably between 1,500 and 150,000, and more preferably between 2,000 and 100,000. A weight-average molecular weight of 2,000 or higher can improve tack-free performance and / or resolution. Furthermore, a weight-average molecular weight of 150,000 or lower can improve developability and / or storage stability. The weight-average molecular weight (Mw) can be determined from the standard polystyrene equivalent value obtained by gel permeation chromatography (GPC).

[0051] The alkali-soluble resin content can be, for example, 15 to 60% by mass, preferably 20 to 60% by mass, and more preferably 20 to 55% by mass, based on the solid content relative to the total amount of curable resin composition. A content of 15% by mass or more, preferably 20% by mass or more, can improve the strength of the cured product. Furthermore, a alkali-soluble resin content of 60% by mass or less results in a desirable viscosity and improved processability.

[0052] (Photopolymerizable monomer) The curable resin composition of the present invention may contain a photopolymerizable monomer. Examples of photopolymerizable monomers include compounds having one or more ethylenically unsaturated bonds in their molecules. Photopolymerizable monomers can further impart crosslinking and curability of the cured coating film upon irradiation with active energy rays such as ultraviolet light.

[0053] Examples of compounds used as photopolymerizable monomers include conventionally known polyester (meth)acrylates, polyether (meth)acrylates, urethane (meth)acrylates, carbonate (meth)acrylates, epoxy (meth)acrylates, and the like. Specifically, photopolymerizable monomers include hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate and 2-hydroxypropyl acrylate; diacrylates of glycols such as ethylene glycol, methoxytetraethylene glycol, polyethylene glycol, and propylene glycol; acrylamides such as N,N-dimethylacrylamide, N-methylolacrylamide, and N,N-dimethylaminopropylacrylamide; aminoalkyl acrylates such as N,N-dimethylaminoethyl acrylate and N,N-dimethylaminopropyl acrylate; polyhydric alcohols such as hexanediol, trimethylolpropane, pentaerythritol, dipentaerythritol, and tris-hydroxyethyl isocyanurate, or their ethylene oxide adducts, propylene oxide adducts, or ε- Polyvalent acrylates derived from caprolactone adducts, etc.; polyvalent acrylates such as phenoxyacrylate, bisphenol A diacrylate, and ethylene oxide adducts or propylene oxide adducts of these phenols; polyvalent acrylates derived from glycidyl ethers such as glycerin diglycidyl ether, glycerin triglycidyl ether, trimethylolpropane triglycidyl ether, and triglycidyl isocyanurate; and, not limited to the above, acrylates obtained by directly acrylateting polyols such as polyether polyols, polycarbonate diols, hydroxyl-terminated polybutadienes, and polyester polyols, or by urethane acrylate obtained via diisocyanate, as well as melamine acrylate, and at least one of each methacrylate corresponding to the acrylate can be appropriately selected and used.

[0054] The content of photopolymerizable monomers can be, for example, 15% by mass or less on a solid content basis relative to the total amount of curable resin composition, preferably 1 to 15% by mass, more preferably 1 to 10% by mass, and even more preferably 3 to 9% by mass.

[0055] (Photopolymerization initiator) The curable resin composition of the present invention may contain one or more photopolymerization initiators. Examples of photopolymerization initiators include oxime ester-based photopolymerization initiators, bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)- Bis-acylphosphine oxides such as 2,4,4-trimethylpentylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, and bis-(2,4,6-trimethylbenzoyl)-phenylphosphine oxide; 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphine methyl ester, and 2-methylbenzoyldiphenylphosphine Monoacylphosphine oxides such as oxides, isopropyl pivaloylphenylphosphinate, and 2,4,6-trimethylbenzoyldiphenylphosphine oxide; 1-hydroxycyclohexylphenyl ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)-benzyl]phenyl}-2-methyl-propan-1-one, 2-hydroxy-2-methyl Hydroxyacetophenones such as til-1-phenylpropan-1-one; benzoins such as benzoin, benzyl, benzoin methyl ether, benzoin ethyl ether, benzoin n-propyl ether, benzoin isopropyl ether, and benzoin n-butyl ether; benzoin alkyl ethers; benzophenones such as benzophenone, p-methylbenzophenone, Michlar's ketone, methylbenzophenone, 4,4'-dichlorobenzophenone, and 4,4'-bisdiethylaminobenzophenone;Acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-1-propanone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1, 2-(dimethylamino)-2-[(4-methylphenyl)methyl)-1-[4-(4-morpholinyl)phenyl]-1-bu Acetophenones such as tanone and N,N-dimethylaminoacetophenone; thioxanthones such as thioxanthone, 2-ethylthioxanthone, 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2-chlorothioxanthone, and 2,4-diisopropylthioxanthone; anthraquinone, chloroanthraquinone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 1-chloroanthraquinone, and 2-amylanthraquinone Anthraquinones such as 2-aminoanthraquinone; ketals such as acetophenone dimethyl ketal and benzyl dimethyl ketal; benzoic acid esters such as ethyl-4-dimethylaminobenzoate, 2-(dimethylamino)ethyl benzoate, and p-dimethylbenzoate ethyl ester; 1,2-octanedione, 1-[4-(phenylthio)-,2-(O-benzoyloxime)], etanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-,1-(O-acetylo Examples include oxime esters such as xime; titanosenes such as bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrole-1-yl)phenyl)titanium and bis(cyclopentadienyl)-bis[2,6-difluoro-3-(2-(1-pyr-1-yl)ethyl)phenyl]titanium; phenyl disulfide 2-nitrofluorene, butyroin, anisoin ethyl ether, azobisisobutyronitrile, and tetramethylthiuram disulfide.

[0056] (Hardening agent) The curable resin composition of the present invention may contain a curing agent. Examples of curing agents include phenolic resins, polycarboxylic acids and their acid anhydrides, cyanate ester resins, activated ester resins, maleimide compounds, and alicyclic olefin polymers. The curing agent can be used alone or in combination of two or more.

[0057] (Coloring agent) The curable resin composition of the present invention may contain a coloring agent. Known coloring agents such as red, blue, green, yellow, black, and white can be used, and may be pigments, dyes, or colorants. However, from the viewpoint of reducing environmental impact and affecting human health, it is preferable that the coloring agent does not contain halogens.

[0058] There are no particular restrictions on the amount of colorant, but typically, it is preferably 10 parts by mass or less, and more preferably 0.1 to 7 parts by mass, per 100 parts by mass of curable resin, on a solid content basis.

[0059] (Organic solvents) The curable resin composition of the present invention may contain an organic solvent for purposes such as preparing the composition and adjusting the viscosity when applying it to a substrate or carrier film (hereinafter also referred to as the "first film"). As organic solvents, known and commonly used organic solvents can be used, such as ketones like methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons like toluene, xylene, and tetramethylbenzene; glycol ethers like cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, diethylene glycol monomethyl ether acetate, and tripropylene glycol monomethyl ether; esters like ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, and propylene carbonate; aliphatic hydrocarbons like octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, and solvent naphtha. These organic solvents can be used individually or in combination of two or more types.

[0060] (Other optional components) Furthermore, the curable resin composition of the present invention may contain other additives known and commonly used in the field of electronic materials. Examples of other additives include thermal polymerization inhibitors, ultraviolet absorbers, silane coupling agents, plasticizers, flame retardants, antistatic agents, anti-aging agents, antibacterial and antifungal agents, defoaming agents, leveling agents, thickeners, adhesion promoters, thixotropic agents, photoinitiator aids, sensitizers, thermoplastic resins, organic fillers, mold release agents, surface treatment agents, dispersants, dispersion aids, surface modifiers, stabilizers, phosphors, AB-type or ABA-type block copolymers, and the like.

[0061] [Dry film] The curable resin composition of the present invention can be formed into a dry film. The dry film of the present invention has a first film and a resin layer made of the curable resin composition of the present invention formed on at least one of the front and back surfaces of the first film. The first film in the present invention is adhered to the resin layer made of the curable resin composition, and is at least adhered to the resin layer when it is laminated onto a substrate (described later) so that the resin layer side of the dry film is in contact with it and integrally molded. The first film may be peeled off from the resin layer in a post-lamination process. In particular, in the present invention, it is preferable to peel it off from the resin layer in a post-exposure process. When forming a dry film, first, the curable resin composition of the present invention is diluted with the above-mentioned organic solvent to adjust it to an appropriate viscosity, and then applied to a first film to a uniform thickness using a comma coater, blade coater, lip coater, rod coater, squeeze coater, reverse coater, transfer roll coater, gravure coater, spray coater, etc. After that, the applied composition can be dried at a temperature of, for example, 40 to 130°C for 1 to 30 minutes to form a resin layer. There are no particular restrictions on the coated film thickness, but generally, the film thickness after drying can be appropriately selected in the range of 3 to 150 μm, preferably 5 to 60 μm.

[0062] As the first film, a plastic film can be used, such as polyester film like polyethylene terephthalate (PET), polyimide film, polyamide-imide film, polypropylene film, or polystyrene film. A laminate of these films can also be used as the first film. There are no particular restrictions on the thickness of the first film, but it can generally be appropriately selected in the range of 10 to 150 μm, and more preferably in the range of 15 to 130 μm.

[0063] After forming a resin layer made of the curable resin composition of the present invention on the first film, it is preferable to further laminate a peelable cover film (hereinafter also referred to as the "second film") on the surface of the resin layer for purposes such as preventing dust from adhering to the surface of the resin layer. The second film in the present invention refers to a film that is peeled off from the resin layer before lamination when integrally forming by laminating a dry film onto a substrate by heating or the like so that the resin layer side of the dry film is in contact with it. Examples of peelable second films include polyethylene film, polytetrafluoroethylene film, polypropylene film, surface-treated paper, etc. The second film only needs to have an adhesive strength that is less than the adhesive strength between the resin layer and the first film when the second film is peeled off.

[0064] In addition, in the present invention, a resin layer may be formed by applying and drying the curable resin composition of the present invention on the second film, and then laminating the first film on its surface. That is, in the present invention, when manufacturing a dry film, either the first film or the second film may be used as the film to which the curable resin composition of the present invention is applied.

[0065] [Printed wiring board] The printed circuit board of the present invention is used in various electronic devices and has a cured product obtained from the curable resin composition of the present invention or from the resin layer of a dry film. The cured product obtained from the curable resin composition containing the dispersion of the present invention effectively prevents cracks and peeling, particularly those caused by differences in thermal expansion coefficients with respect to the substrate.

[0066] The cured product of the present invention can be manufactured, for example, as follows. That is, the curable resin composition of the present invention is adjusted to a viscosity suitable for the coating method using the above-mentioned organic solvent, and then applied to a substrate by methods such as dip coating, flow coating, roll coating, bar coating, screen printing, or curtain coating. After that, the organic solvent contained in the composition is evaporated and dried (pre-dried) at a temperature of 60 to 100°C to form a tack-free resin layer (cured product) on the substrate. In the case of a dry film, the resin layer on the substrate is formed by laminating the dry film onto the substrate using a laminator or the like so that the resin layer of the dry film comes into contact with the substrate.

[0067] Specifically, the above-mentioned substrates include printed circuit boards and flexible printed circuit boards with circuits pre-formed using copper, as well as copper-clad laminates using materials such as paper phenol, paper epoxy, glass cloth epoxy, glass polyimide, glass cloth / nonwoven epoxy, glass cloth / paper epoxy, synthetic fiber epoxy, fluororesin / polyethylene / polyphenylene ether, polyphenylene oxide / cyanate, metal substrates, polyimide substrates such as polyimide films, PET substrates such as PET films, polyethylene naphthalate (PEN) films, glass substrates, ceramic substrates, wafers, and the like.

[0068] The volatilization drying performed after applying the curable resin composition of the present invention can be carried out using a hot air circulation drying oven, an IR oven, a hot plate, a convection oven, etc. (a method in which hot air inside the dryer is brought into countercurrent contact with a heat source equipped with a steam-heated air heating method, or a method in which hot air is blown onto the support from a nozzle).

[0069] The lamination of the dry film onto the substrate is preferably carried out under pressure and heat using a vacuum laminator or the like. By using such a vacuum laminator, even if the surface of the circuit board has irregularities, the resin layer of the dry film adheres closely to the surface of the circuit board, preventing the inclusion of air bubbles and improving the ability to fill in depressions on the substrate surface. The pressure conditions are preferably around 0.1 to 2.0 MPa, and the heating conditions are preferably around 40 to 120°C.

[0070] During exposure, the cured material side of the substrate is selectively exposed with active energy rays through a photomask with a predetermined pattern. Then, in the case of a dry film, the first film is peeled off from the dry film, and the unexposed areas are developed with a dilute alkaline aqueous solution (for example, a 0.3-3% by mass sodium carbonate aqueous solution) to form the pattern of the cured material. In the case of a dry film, exposure can be performed without peeling off the first film from the dry film, or, as long as the properties are not impaired, the first film may be peeled off from the dry film before exposure, and the exposed resin layer may be exposed and developed.

[0071] Furthermore, by irradiating the cured material with active energy rays and then heat-curing it (for example, at 100-220°C), or by irradiating it with active energy rays after heat curing, or by performing final finishing curing (main curing) by heat curing alone, it is possible to form a cured material with excellent properties such as adhesion and hardness.

[0072] The exposure machine used for the above-mentioned active energy ray irradiation can be any device equipped with a high-pressure mercury lamp, ultra-high-pressure mercury lamp, metal halide lamp, mercury short-arc lamp, etc., that irradiates ultraviolet light in the range of 350 to 450 nm. Furthermore, a direct writing device (for example, a laser direct imaging device that directly draws images with a laser using CAD data from a computer) can also be used. The lamp light source or laser light source of the direct writing device can have a maximum wavelength in the range of 350 to 450 nm. The exposure amount for image formation varies depending on the film thickness, etc., but is generally 10 to 1000 mJ / cm². 2Preferably 20-800 mJ / cm² 2 It can be within the range of

[0073] The above-mentioned development method can be the dipping method, shower method, spray method, brush method, etc., and alkaline aqueous solutions such as potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium phosphate, sodium silicate, ammonia, and amines can be used as the developing solution.

[0074] The cured product of the present invention obtained as described above can be used as a solder resist layer for printed circuit boards and the like without cracks or peeling. Furthermore, the dispersion and curable resin composition containing the dispersion of the present invention have high stability over time, making them effective in improving yield during printed circuit board manufacturing.

[0075] Therefore, the curable resin composition of the present invention and the dry film having a resin layer obtained from this curable resin composition can be suitably used to form a cured product on a printed wiring board used for semiconductor packaging and the like, more preferably used to form a permanent film, and even more preferably used to form a solder resist, an interlayer insulating layer, or a coverlay. [Examples]

[0076] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In the following, "parts" and "%" all refer to mass unless otherwise specified.

[0077] The dispersions for the examples and comparative examples were prepared by blending the various components shown in Table 1 in the indicated proportions (mass%). The values ​​in Table 1 are based on solid content. Furthermore, the components *1 to *5 in Table 1 are as follows: *1: Precipitating barium sulfate 100 (manufactured by Sakai Chemical Industry Co., Ltd., standard grade, particle size D50 = 0.6 μm) *2: DISPERBYK-140 (manufactured by BIC Chemie Japan Co., Ltd., solution of alkylammonium salt of acidic polymer, non-volatile content 52%, solvent: methoxypropyl acetate, amine value 76 mg KOH / g, acid value 73 mg KOH / g) *3: DISPERBYK-164 (manufactured by BIC Chemie Japan Co., Ltd., solution of high molecular weight block copolymer with pigment affinity groups, non-volatile content 60%, solvent: butyl acetate, amine value 18 mg KOH / g) *4: Dipropylene glycol monomethyl ether (DPM) *5: Diethylene glycol monoethyl acetate (Jukisol CA)

[0078] <Measurement and evaluation of viscosity> The viscosity immediately after mixing each component was measured using a cone-plate viscometer (TVE-33H, manufactured by Toki Sangyo Co., Ltd.) with a 3°×R9.7 cone rotor, at 50°C, 100 rpm, and 30 seconds, in accordance with the viscosity measurement method using a 10-cone-plate rotational viscometer specified in JIS Z 8803:2011. The criteria for evaluating viscosity are as follows. ○: Less than 3 Pa·s (suitable for dispersion processes) △: 3 Pa·s or more and less than 10 Pa·s (dispersion process can be performed) ×: Above 10 Pa·s (Dispersion process cannot be performed)

[0079] <Measurement of dispersion and evaluation of stability over time> A dispersion was manufactured through a dispersion process, and the degree of dispersion was measured immediately after manufacture, and at 5, 14, 30, and 60 days later to confirm its stability over time. The dispersion was stored at room temperature (20°C ± 5°C) from the time of manufacture until 60 days later. The dispersion process was carried out using a bead mill until the degree of dispersion, judged by the value of 5 beads, was 5 μm or less. The degree of dispersion was measured using a 0-50 μm grind gauge, in accordance with JIS K5600-2-5:1999 Part 2-Section 5: Methods for Determining Dispersion. The evaluation criteria for the degree of dispersion are as follows. ○: The dispersion degree, judged by the 5-particle value, is less than 7.5 μm. △: The dispersion, judged by the value of 5 particles, is between 7.5 μm and 10 μm. ×: Dispersion degree judged by 5-particle values ​​is 10 μm or larger.

[0080] [Table 1]

[0081] As shown in Table 1, Examples 1 to 6, which contain a barium sulfate content in the range of 50 to 80% by mass relative to the total volume of the dispersion, and are dispersions containing a branched polyamine dispersant, a polyurethane dispersant, and a solvent, can be circulated in a mixed state during the dispersion process using a bead mill, and the dispersibility is maintained from immediately after dispersion through the dispersion process up to 60 days later. In contrast, Comparative Example 1, which used only a dispersant containing a branched polyamine, did not achieve a viscosity that allowed for circulation during the dispersion process using a bead mill when mixed with barium sulfate, the dispersant, and the solvent, and therefore could not be evaluated afterward. Furthermore, Comparative Example 2, which used only a dispersant containing polyurethane, achieved a viscosity that allowed for circulation during the dispersion process using a bead mill when mixed, and was able to undergo the dispersion process, but its dispersibility deteriorated after 30 days, and its long-term stability was insufficient. Furthermore, in Comparative Example 3, which contained 90% by mass of barium sulfate, although a dispersant containing a branched polyamine and a dispersant containing polyurethane were used in combination, the viscosity of the mixed dispersant and solvent did not reach a level that allowed for circulation during the dispersion process using a bead mill, and subsequent evaluation was not possible. The barium sulfate content is considered to be excessively high. As shown above, the results in Table 1 demonstrate that the dispersion of the present invention exhibits excellent dispersibility and long-term stability of barium sulfate.

Claims

1. A dispersion comprising barium sulfate, a dispersant having a branched polyamine, a dispersant having polyurethane, and a solvent, wherein the barium sulfate content is 50 to 80% by mass of the total volume of the dispersion.

2. The dispersion according to claim 1, wherein the average particle size of barium sulfate in the dispersion is 0.1 μm to 5 μm.

3. A curable resin composition characterized by comprising a curable resin and the dispersion liquid according to claim 1 or 2.

4. A dry film comprising a first film and a resin layer formed from the curable resin composition according to claim 3, laminated on at least one surface of the first film.

5. A cured product characterized by being obtained by curing the curable resin composition of claim 3.

6. A cured product characterized by having cured resin layer of the dry film described in claim 4.

7. A printed circuit board characterized by comprising the cured product described in claim 5.

8. A printed circuit board characterized by comprising the cured product described in claim 6.

Citation Information

Patent Citations

  • Photosensitive resin composition

    JP2000181058A

  • Process for preparing resin varnish

    JP2002080818A